ANALYSIS OF TRANSFORMATIONAL LEADERSHIP OF SUB-DISTRICT HEAD IN INCREASING EMPLOYEE WORK MOTIVATION AT TERING DISTRICT OFFICE, WEST KUTAI REGENCY - Thotok Suprapto; Cathas Teguh Prakoso; Santi Rande; Daryono; Jamal Amin; Kus Indarto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The success of public services at the sub-district level depends heavily on the work motivation of its personnel. This study analyzes the implementation of transformational leadership by the Sub-District Head (Camat) of Tering in increasing employee work motivation at the Tering Sub-District Office, Kutai Barat Regency, and identifies the inhibiting factors. A qualitative case-study approach was employed, with data gathered through in-depth interviews with the Camat, the Sub-District Secretary, Section Heads, permanent and contract staff, and service users, supported by observation and documentation, and analyzed using Creswell's qualitative model. The findings show that the four dimensions of transformational leadership practiced by the Camat effectively shifted employee work orientation from external motivation (fear of sanctions) to internal motivation grounded in moral responsibility. Leading by example eased rigid bureaucratic communication, while inspirational motivation, intellectual stimulation, and individualized attention fostered a sense of belonging, initiative, and commitment among staff. Nevertheless, this leadership's effectiveness remains constrained by the rigid, instructional style of several Section Heads and by external factors such as inadequate infrastructure and poor internet connectivity (blank spots) typical of the remote Kutai Barat region. Strong solidarity and family-like relationships among staff serve as vital social capital in sustaining public service delivery despite these constraints.